Diversity and distribution of small-sized planktonic ciliate communities in the East China Sea - Chen, Wei-Ting; Lin, Yun-Chi; Tsai, Sheng-Fang; Chiang, Kuo-Ping (Frontiers in Marine Science, 2024)
Ciliates are an important ecological component in the microbial food web, but few studies have been conducted on the spatial distribution of small plankton ciliate communities in the East China Sea (ECS). Investigating ciliate communities using conventional morphological approaches is particularly difficult for the small, fragile, and naked species. Therefore, we applied DNA metabarcoding analysis to explore the spatial pattern of small-sized planktonic ciliates community structure within the surface, deep chlorophyll maximum (DCM), and bottom layers. Results showed the cosmopolitan species, Leegaardiella sp., was dominant and widespread in the ECS. The relative abundance of the mixotrophic family Tontonnidae decreased in the deeper layer. We characterized water masses of the ECS using environmental variables. In nano-sized ciliate communities, non-metric multidimensional scaling (NMDS) plots revealed a correlation with temperature, salinity, density, and depth.The circulation patterns were similar to cluster analysis results, suggesting hydrographic conditions shaped small ciliate community composition.